Access to the internet and regional structures: the case of Italy (2016)
I study the effects of Internet access on regional structures and provide some insights into the complex question of the role of technology in regional development. The paper analyzes the distribution of access to the Internet in Italy, highlighting the differences among regions and sub-regional areas and with respect to categories of users. This is an aspect of the so-called "digital divide". I concentrate on the stability and change of regional structures in Italy, pointing at conclusions of general relevance. My analysis confirms the dynamism of the regions of the socalled "Third Italy" and the fundamental distinction between the North-Center with respect to the South, the Italian Mezzogiorno. My preliminary conclusions on the effects of the Internet in promoting economic development suggest lines for further investigation.